Effects of Betaine Aldehyde Dehydrogenase-Transgenic Soybean on Phosphatase Activities and Rhizospheric Bacterial Community of the Saline-Alkali Soil. (4th September 2016) - Nie, Ying; Wang, Da-qing; Zhao, Guang; Yu, Song; Wang, Hong-yan
Abstract : The development of transgenic soybean has produced numerous economic benefits; however the potential impact of root exudates upon soil ecological systems and rhizospheric soil microbial diversity has also received intensive attention. In the present study, the influence of saline-alkali tolerant transgenic soybean of betaine aldehyde dehydrogenase on bacterial community structure and soil phosphatase during growth stages was investigated. The results showed that, compared with nontransgenic soybean as a control, the rhizospheric soil pH of transgenic soybean significantly decreased at the seedling stage. Compared to HN35, organic P content was 13.5% and 25.4% greater at the pod-filling stage and maturity, respectively. The acid phosphatase activity of SRTS was significantly better than HN35 by 12.74% at seedling, 14.03% at flowering, and 59.29% at podding, while alkaline phosphatase achieved maximum activity in the flowering stage and was markedly lower than HN35 by 13.25% at pod-filling. The 454 pyrosequencing technique was employed to investigate bacterial diversity, with a total of 25, 499 operational taxonomic units (OTUs) obtained from the 10 samples. Notably, the effect of SRTS on microbial richness and diversity of rhizospheric soil was marked at the stage of podding and pod-filling. Proteobacteria, Acidobacteria, and Actinobacteria were the dominant phyla among all samples. Compared with HN35, the relative abundance of Proteobacteria was lower by 2.01%, 2.06%, and 5.28% at the stage of seedling, at pod-bearing, and at maturity. In genus level, the relative abundance of Gp6, Sphingomonas sp., and GP4 was significantly inhibited by SRTS at the stage of pod-bearing and pod-filling.